Análise morfológica e imunohistoquímica de placentas caninas provenientes de eutocia e distocia - Costa, Isadora Frazon [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Placentation and the development of fetal membranes in dogs are currently studied extensively, since the knowledge of morphology of the placenta enables properly recognize pathological changes and its correlation with neonatal viability. We aimed to characterize morphologically and immunohistochemically placentas of bitches from eutocia and dystocia. For that 80 placentas were collected and classified according to the type of delivery into three experimental groups,GN (n = 40) placentas obtained from normal delivery, GC (n = 28) placentas obtained from cesarean section and GAUP (n = 12) placentas obtained from bitches with uterine atony. 1cm x 1cm pieces were cut from the region near the umbilical cord and stored in 10% buffered formalin for 48 hours following, were transferred to 70% alcohol, which remained until processing for histopathological and immunohistochemical study. In this research, areas of hemorrhage, necrosis, inflammation and calcification were observed in the placentas in all three groups. Hemorrhagic areas were identified in the placental parenchyma in all groups, without significant difference. The evident necrosis in the placenta maternal face was constant in the groups, we observe areas and spots of necrosis in the lamellar region in GC and GAUP, but those findings were not statistically significant when compared to GN. Inflammation was rarely observed in the GN and it was observed in a few samples in the GC, however it was predominant in samples from GAUP. Calcification spots were observed in GC and GAUP. In the studied groups, discrete alterations were observed when histological integrity of marginal hematomas was evaluated. In GN the immunostaining for vimentin proved to be intense and homogeneous throughout lamellar zone, however this was not observed in GC and GAUP, which presented immunostaining characterized by variation of intensity. For cytokeratin there was no difference between experimental groups. The RP...

A placentação e o desenvolvimento das membranas fetais na espécie canina atualmente são estudados de forma extensiva, já que o conhecimento da morfologia da placenta possibilita reconhecer corretamente alterações patológicas e sua possível correlação com a viabilidade neonatal. O presente estudo tem como objetivo a caracterização morfológica e imunohistoquímica de placentas de cadelas provenientes de eutocia e distocia. Para o desenvolvimento deste experimento foram coletadas 80 placentas, de acordo com o tipo de parto as placentas foram divididas em três grupos experimentais, GN (n=40) placentas obtidas de parto normal, GC (n=28) placentas obtidas de cesariana e GAUP (n=12) placentas obtidas de cadelas em atonia uterina primária. Fragmentos 1cm x 1cm foram seccionados da região próxima ao cordão umbilical e armazenados em formol tamponado 10% durante 48 horas, a seguir, foram transferidos para álcool 70%, no qual permaneceram até o processamento para o estudo histopatológico e imunohistoquímico. Foram reconhecidas áreas de hemorragia, necrose, inflamação e calcificação nas placentas dos três grupos estudados. A hemorragia no parênquima placentário foi identificada em todos os grupos experimentais, não apresentando diferença significativa. A necrose evidenciada junto a face materna foi uma constante nos grupos avaliados, entretanto foram observados na região lamelar focos e áreas de necrose no GC e GAUP, porém estes achados não foram estatisticamente relevantes quanto a comparação ao GN. A inflamação foi raramente observada no GN, esteve pouco presente no GC e predominou nas amostras placentárias do GAUP. Os focos de calcificação identificados foram mais notórios no GC e GAUP. Nos grupos estudados foram observadas alterações discretas quanto a integridade histológica dos hematomas marginais. Nas placentas GN a imunomarcação para vimentina mostrou-se intensa e homogênea em toda zona lamelar, fato...
Morphological and immunohistochemical analysis of canine placentas from eutocia and dystocia
Keywords: Neonatologia veterinária; Animais domesticos - Reprodução; Cães; Placenta - Pesquisa; Imunohistoquímica; Distonia muscular deformante; Progesterona; Dystonia musculorum deformans; Veterinary neonatology